Testimonies of Communication in Dementia Care - Campbell, Grant D.; Dalmer, Nicole; Andrews, Jason (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2019)
This paper presents a study of recorded conversations, qualitative interviews, and published memoirs to articulate the role of professional information services in answering the needs of persons caring for family members living with dementia. The data from these sources reveals evidence of working naïve classifications based on images of ritual, paradox, contrast, synchrony and stability. The findings suggest that information services need to align with caregivers’ working classifications, and that information, when appropriately delivered, plays a significant role in re-establishing temporary periods of stability in the caregiving relationship.